2007
DOI: 10.1016/j.atmosenv.2006.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Flux estimates and OH reaction potential of reactive biogenic volatile organic compounds (BVOCs) from a mixed northern hardwood forest

Abstract: Diurnal branch-level emission rates of biogenic volatile organic compounds (BVOC) including isoprene, monoterpenes (MT), and sesquiterpenes (SQT) were determined at the University of Michigan Biological Station for the tree species red maple (Acer rubrum), red oak (Quercus rubra), paper birch (Betula papyrifera), white pine (Pinus strobus), and big tooth aspen (Populus grandidentata). These emission rates were combined with detailed biomass distribution and meteorological data and incorporated into the canopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…Emission studies were performed by enclosing individual branches of pine trees with lighttransparent Tedlar of Teflon bags. Detailed descriptions of the experimental protocol, materials used, flow conditions, removal of ozone in the purge and sample air, and monitoring of environmental data have been published previously (20)(21)(22)31) and are only summarized here. After installation of the enclosure, the branch was allowed to acclimate to the enclosure conditions for 0.5-1 day, which also allowed any potential disturbance-induced BVOC bursts to subside and be purged out of the enclosure before sampling began.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission studies were performed by enclosing individual branches of pine trees with lighttransparent Tedlar of Teflon bags. Detailed descriptions of the experimental protocol, materials used, flow conditions, removal of ozone in the purge and sample air, and monitoring of environmental data have been published previously (20)(21)(22)31) and are only summarized here. After installation of the enclosure, the branch was allowed to acclimate to the enclosure conditions for 0.5-1 day, which also allowed any potential disturbance-induced BVOC bursts to subside and be purged out of the enclosure before sampling began.…”
Section: Methodsmentioning
confidence: 99%
“…Both automated systems typically collected 10-12 emission samples per day over a 2-3 day period for each enclosure experiment. SQT were identified based on their mass spectra and by comparison of their chromatographic elution order (32); quantifications were achieved after determining the analyte recoveries and calibrating the GC/FID response with n-alkane (33) and SQT (21) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Speciated monoterpene measurements at this field site have been infrequently reported in the literature. Branch enclosure measurements made by Ortega et al (2007) showed that the dominant light-dependent monoterpene emitted from all deciduous species was transocimene with conifers emitting α-pinene, β-pinene, camphene, d-limonene, and para-cymene, among other monoterpenes. Kim et al (2009) reported speciated monoterpenes from canister measurements taken in their 2005 study.…”
Section: G D Edwards Et Al: a Disjunct Eddy Accumulation System Fomentioning
confidence: 99%
“…Guenther et al, 1995;Lathière et al, 2006;Seco et al, 2007) with an associated strong impact on atmospheric chemistry. BVOC consume or produce tropospheric ozone, depending on atmospheric physicochemical conditions like the levels of NO x , and influence the levels of OH and hence methane lifetime (Derwent et al, 1995;Atkinson, 2000;Poisson et al, 2000;Ortega et al, 2007). BVOCs are also known to initiate and foster the production of secondary organic aerosols (SOA, Hoffmann et al, 1997;O'Dowd et al, 2002;Kulmala et al, 2004) that scatter and absorb radiation and act as cloud condensation nuclei.…”
Section: Introductionmentioning
confidence: 99%